Composite gel electrolyte diaphragm as well as preparation method and application thereof

By coating ceramic and gelled functional coatings on the polymer substrate of the lithium-ion battery separator to form a multi-layer structure, the problem of insufficient mechanical and thermal stability of the existing separator under high temperature and high magnification conditions is solved, and better comprehensive performance is achieved.

CN119920953APending Publication Date: 2025-05-02HU ZHOU YAO NING GU TAI DIAN CHI YAN JIU YUAN YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411928674.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing gel electrolyte separators have insufficient mechanical energy and thermal stability under high temperature, high rate discharge and long cycle conditions, which limits the development of lithium-ion batteries in high safety and long life applications.

Method used

A composite material of PVDF-HFP and aramid fiber of a specific ratio is used as the substrate, and the ceramic coating and gelling functional coating are successively coated on both sides to form a multi-layer structure to improve the thermal stability, mechanical strength and electrochemical properties of the membrane.

Benefits of technology

The thermal stability, mechanical strength and long cycle stability of the diaphragm are significantly improved, and its comprehensive performance is optimized, so that it can show excellent performance under high temperature, high rate discharge and long cycle conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920953A_ABST
    Figure CN119920953A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion batteries, and discloses a composite gel electrolyte diaphragm as well as a preparation method and application thereof, the composite gel electrolyte diaphragm comprises a polymer base material, and a ceramic coating and a gelatinization functional coating which are sequentially coated on two surfaces of the polymer base material; the polymer base material contains PVDF-HFP (Polyvinylidene Fluoride-Hexafluoropropylene) and aramid fiber in a weight ratio of (5-6): 1; and the gelatinized functional coating contains gel and PVDF-HFP (Polyvinyl Fluoride-Hexafluoropropylene) in a weight ratio of 1: (2-3). The composite gel electrolyte diaphragm provided by the invention has excellent thermal stability, mechanical strength and long cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium electronic batteries, and in particular to a composite gel electrolyte diaphragm and a preparation method and application thereof. Background Art

[0002] With the rapid development of electric vehicles, renewable energy storage systems and portable electronic devices, lithium-ion batteries, as a high-efficiency energy storage device, have received increasing attention. Lithium-ion batteries have the advantages of high energy density, long cycle life and low self-discharge rate, and are widely used in various electronic devices. However, with the continuous improvement of battery performance requirements, some problems of traditional liquid electrolytes, such as flammability, leakage risk and battery safety issues, have gradually been exposed, limiting the further development of lithium-ion batteries in high-safety and long-life applications.

[0003] In order to solve these problems, gel electrolyte separators have become a hot topic of research in recent years. Gel electrolyte separators combine the advantages of solid electrolytes and liquid electrolytes, which can not only effectively block the growth of lithium dendrites, but also maintain high ionic conductivity. However, the existing gel electrolyte separators still have the problem of insufficient mechanical energy and thermal stability under high temperature, high rate discharge and long cycle conditions. Commonly used polymer materials such as polyvinylidene fluoride (PVDF) and / or polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) have good chemical stability, but their mechanical strength and thermal stability are easily degraded under high temperature conditions.

[0004] To overcome these challenges, researchers have proposed a variety of optimization schemes, including adding inorganic nanofillers to polymer substrates, modifying polymers, and using multifunctional composite coatings. However, these schemes still have some technical bottlenecks, such as insufficient uniformity of the coating, poor stability of the multilayer structure, and further room for improvement of the comprehensive performance.

[0005] Therefore, there is an urgent need for a new gel electrolyte membrane that can significantly improve its mechanical strength, thermal stability and cycle life while ensuring high ionic conductivity. Summary of the invention

[0006] The purpose of the present invention is to provide a composite gel electrolyte membrane having excellent thermal stability, mechanical strength and long cycle stability.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composite gel electrolyte membrane, which comprises a polymer substrate, and a ceramic coating and a gelling functional coating sequentially coated on both sides of the polymer substrate;

[0008] The polymer substrate contains PVDF-HFP and aramid fiber in a weight ratio of 5-6:1; the gelling functional coating contains a gelling agent and PVDF-HFP in a weight ratio of 1:2-3.

[0009] The second aspect of the present invention provides a method for preparing the composite gel electrolyte membrane described in the first aspect, the method is performed using the electrolyte membrane described in the first aspect, and comprises the following steps:

[0010] (1) in the presence of an organic solvent I, the components in the composition A are first mixed to obtain a mixture I; the mixture I is sequentially subjected to a casting process, a drying process I and a molding process to obtain the polymer substrate;

[0011] The composition A contains PVDF-HFP, aramid fiber, and optionally polyimide and optionally diisocyanate;

[0012] (2) performing a second mixing of the ceramic material and the organic solvent II to obtain a mixture II; applying the mixture II on both sides of the polymer substrate by a roller coating method, and performing a drying treatment II to obtain an intermediate diaphragm product;

[0013] (3) In the presence of an organic solvent III, the gelling agent and PVDF-HFP are mixed for a third time to obtain a mixture III; the mixture III is coated on both sides of the intermediate diaphragm product by a dip coating method, and a drying treatment III is performed to obtain the composite gel electrolyte diaphragm.

[0014] The third aspect of the present invention provides use of the composite gel electrolyte membrane described in the second aspect in a lithium ion battery.

[0015] The present invention forms a multilayer structure by introducing a ceramic coating and a gelling functional coating, so that the diaphragm exhibits excellent comprehensive performance under high temperature, high rate discharge and long cycle conditions; the present invention adopts a composite material of PVDF-HFP and aramid fiber in a specific ratio as a substrate, which significantly improves the thermal stability and mechanical strength of the diaphragm.

[0016] The present invention combines tape casting, roller coating and dip coating processes to precisely control the coating film thickness and porosity, ensuring the uniformity and functionality of the diaphragm; the gelled functional coating prepared by using a gelling agent and PVDF-HFP improves the ionic conductivity and electrolyte compatibility of the diaphragm. Therefore, the technical solution of the present invention can simultaneously optimize the thermal stability, mechanical strength and electrochemical performance of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic diagram of the structure of the composite gel electrolyte membrane provided by the present invention. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] The PVDF-HFP described in the present invention refers to polyvinylidene fluoride-hexafluoropropylene. The LATP ceramic refers to lithium aluminum titanium phosphate ceramic. The LLZTO ceramic refers to tantalum-doped lithium lanthanum zirconate ceramic.

[0020] As mentioned above, the first aspect of the present invention provides a composite gel electrolyte membrane, which comprises a polymer substrate, and a ceramic coating and a gelling functional coating sequentially coated on both sides of the polymer substrate;

[0021] The polymer substrate contains PVDF-HFP and aramid fiber in a weight ratio of 5-6:1; the gelling functional coating contains a gelling agent and PVDF-HFP in a weight ratio of 1:2-3.

[0022] Figure 1 This is a schematic diagram of the structure of the composite gel electrolyte membrane provided by the present invention.

[0023] Preferably, the PVDF-HFP meets the following conditions: HFP content 5-10wt%, weight average molecular weight 300,000-1,000,000, particle size D50 value 3-10μm, melting point 140-160°C.

[0024] Preferably, the ceramic coating is selected from at least one of alumina ceramics, boehmite ceramics, zirconia ceramics, LATP ceramics, and LLZTO ceramics. More preferably, the ceramic coating is alumina ceramics.

[0025] Preferably, the gelling agent is selected from at least one of polyethers, polyacrylonitrile, polymers of acrylic acid and its lipids, polyvinyl chloride, polyamide, cellulose, polyethylene oxide, polypropylene oxide, and polyvinyl acetate.

[0026] Preferably, the gelling agent has the following conditions: a weight average molecular weight of 100,000-1,000,000 and a melting point of 60-70°C.

[0027] The inventors have found that the use of the gelling agent under the above preferred conditions can produce a composite gel electrolyte membrane with better thermal stability, mechanical strength and long cycle stability. According to a particularly preferred embodiment, the gelling agent is polyethylene oxide (PEO).

[0028] The gelling functional coating of the composite gel electrolyte diaphragm provided by the present invention contains a gelling agent and PVDF-HFP in a specific weight ratio at the same time. The inventors have found that the combination of the gelling agent and PVDF-HFP as necessary components of the gelling functional coating can significantly improve the liquid absorption rate and ion conductivity of the diaphragm and form a gel with the organic solvent in the electrolyte, thereby achieving the effect of improving the rate performance and cycle performance of the battery cell.

[0029] Particularly preferably, the aramid fiber has a length of 50-100 μm.

[0030] Preferably, the polymer substrate further contains polyimide, and the content of the polyimide is 3-10 wt %, more preferably 4-6 wt %, based on the total weight of the polymer substrate.

[0031] More preferably, the polymer substrate further contains diisocyanate, and the content of the diisocyanate is 1-5 wt %, more preferably 1-3 wt %, based on the total weight of the polymer substrate.

[0032] Particularly preferably, the diisocyanate in the polymer matrix is ​​hexamethylene diisocyanate (HDI). The inventors found that in this preferred case, the composite gel electrolyte membrane provided by the present invention has the advantages of stronger thermal stability, mechanical strength and long cycle stability.

[0033] Preferably, the total thickness of the composite gel electrolyte separator is 10-30 μm, more preferably 15-30 μm.

[0034] Particularly preferably, the thickness ratio of the polymer substrate, the ceramic coating and the gelation functional coating in the composite gel electrolyte membrane is 1:0.1-0.3:0.1-0.3.

[0035] It should be noted that the thickness of the ceramic coating and the gelling functional coating refers to the thickness of the coating on one side of the polymer substrate. In the present invention, the thickness of the ceramic coating on both sides of the polymer substrate is preferably the same, and the thickness of the gelling functional coating on both sides of the polymer substrate is preferably the same.

[0036] Preferably, the porosity of the composite gel electrolyte membrane is 30-70%, more preferably 40-60%; the ion conductivity at 25° C. is >2 mS / cm, preferably >2.5 mS / cm, particularly preferably >3 mS / cm.

[0037] Preferably, the tensile strength of the composite gel electrolyte membrane is ≥150kgf / cm2, more preferably ≥180kgf / cm 2 , especially preferably ≥200kgf / cm2 .

[0038] Preferably, the capacity retention rate of the composite gel electrolyte membrane at 25°C and 1000 charge-discharge cycles is ≥86%, more preferably ≥88%, and particularly preferably ≥90%. The composite gel electrolyte membrane provided by the present invention has excellent long-cycle stability at room temperature of 25°C.

[0039] As mentioned above, the second aspect of the present invention provides a method for preparing the composite gel electrolyte membrane described in the first aspect, comprising the following steps:

[0040] (1) in the presence of an organic solvent I, the components in the composition A are first mixed to obtain a mixture I; the mixture I is sequentially subjected to a casting process, a drying process I and a molding process to obtain the polymer substrate;

[0041] The composition A contains PVDF-HFP, aramid fiber, and optionally polyimide and optionally diisocyanate;

[0042] (2) performing a second mixing of the ceramic material and the organic solvent II to obtain a mixture II; applying the mixture II on both sides of the polymer substrate by a roller coating method, and performing a drying treatment II to obtain an intermediate diaphragm product;

[0043] (3) In the presence of an organic solvent III, the gelling agent and PVDF-HFP are mixed for a third time to obtain a mixture III; the mixture III is coated on both sides of the intermediate diaphragm product by a dip coating method, and a drying treatment III is performed to obtain the composite gel electrolyte diaphragm.

[0044] The present invention combines sol-gel method, roller coating method and dip coating method to accurately control the coating film thickness and porosity, ensure the uniformity and functionality of the composite gel electrolyte membrane, and show more excellent thermal stability and electrochemical performance.

[0045] According to a preferred embodiment, in step (1), the operation of first mixing the components in composition A comprises:

[0046] S1: first stirring PVDF-HFP, polyimide and organic solvent I to obtain material S1;

[0047] S2: performing a second stirring on the material S1 and the aramid fiber to obtain material S2;

[0048] S3: The material S2 is stirred with diisocyanate for a third time to obtain the mixed solution I.

[0049] Preferably, in step (1), the conditions of the tape casting process are controlled so that the coating thickness of the mixture I is 5-20 μm, more preferably 5-15 μm.

[0050] Particularly preferably, in step (1), the conditions of the drying treatment I include: a temperature of 75-85°C and a time of 0.5-1.5 h, more preferably 0.5-1 h.

[0051] Preferably, in step (1), the molding process is performed by hot pressing, and the conditions for hot pressing include: a temperature of 100-120° C. and a time of 0.5-1.5 h, more preferably 0.5-1 h.

[0052] Preferably, in step (2), the second mixing is performed at a pH value of 6.5-7.5.

[0053] Particularly preferably, in step (2), the roller coating conditions are controlled so that the coating thickness of the mixture II is 1-5 μm, more preferably 1-3 μm.

[0054] Preferably, in step (2), the conditions of the drying treatment II include: a temperature of 75-85°C; a time of 0.5-1.5h, more preferably 0.5-1h.

[0055] Preferably, in step (3), the dip-coating conditions are controlled so that the coating thickness of the mixture III is 1-3 μm, more preferably 1-2 μm.

[0056] Preferably, in step (3), the conditions of the drying treatment III include: a temperature of 55-65°C; a time of 0.5-1.5h, more preferably 0.5-1h.

[0057] According to a preferred embodiment, the organic solvent I and the organic solvent III are the same or different, and are independently selected from at least one of N-methylpyrrolidone, acetone, ethyl acetate, and N-methylpyrrolidone.

[0058] Preferably, the organic solvent II is selected from at least one of ethanol, ethylene glycol, propylene glycol, acetone and N-methylpyrrolidone.

[0059] It should be noted that, in the method for preparing the composite gel electrolyte membrane provided by the present invention, the coating thickness of the mixture I, the mixture II and the mixture III all refer to the thickness after drying.

[0060] As mentioned above, the third aspect of the present invention provides the use of the composite gel electrolyte membrane described in the second aspect in a lithium ion battery.

[0061] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, all instruments and raw materials used are commercially available. The thickness of the coatings on both sides of the substrate of the diaphragm products prepared in the following examples and comparative examples are symmetrical and the same.

[0062] PVDF-HFP: purchased from Arkema Series of products;

[0063] Aramid fiber: 50-100 μm in length, purchased from DuPont. Series of products;

[0064] Polyimide: purchased from DuPont, Series of products;

[0065] Polyacrylonitrile: PAN product purchased from Toray Company;

[0066] Cellulose: Cellulose reagent purchased from Sigma-Aldrich;

[0067] Carboxymethyl cellulose: purchased from Dow Chemical Walocel TM Series CMC.

[0068] Example 1

[0069] This example is used to illustrate the preparation method of the composite gel electrolyte membrane of the present invention, which comprises the following steps:

[0070] (1) 500 g of PVDF-HFP and 5 wt % of polyimide (based on the total weight of PVDF-HFP, aramid fiber, and polyimide) were dissolved in 2 L of N-methylpyrrolidone solvent and stirred evenly to form a high-temperature stable mixed solution. The dissolution time was 1 h and the stirring speed was 300 rpm. The aramid fiber was slowly added to the mixed solution and dispersed by ultrasound for 30 min to obtain a mixture I. The mixture I was sequentially subjected to a casting process and a drying process I. The dried polymer film was placed in a hot press for molding to obtain a polymer substrate.

[0071] (2) dissolving 800 g of alumina ceramic powder in 2 L of anhydrous ethanol, adding ammonia water to adjust the pH value to 7.0, and forming a uniform sol by magnetic stirring, namely, mixture II; coating the mixture II uniformly on the upper and lower surfaces of the polymer substrate by roller coating, and performing drying treatment II to obtain an intermediate diaphragm product;

[0072] (3) Dissolve 200 g of the gelling agent and PVDF-HFP in 1 L of N-methylpyrrolidone respectively, mix and stir evenly to form a homogeneous solution, namely, mixture III; apply mixture III evenly on the upper and lower surfaces of the middle diaphragm product by dip coating, and perform drying treatment III to obtain the composite gel electrolyte diaphragm.

[0073] The adopted formula and process parameters are shown in Table 1.

[0074] Example 2-3

[0075] The method of Example 1 is referred to, except that the formulas of the components and the process parameters are different, as shown in Table 1 for details.

[0076] Table 1

[0077]

[0078]

[0079] Example 4

[0080] The method of Example 1 is carried out with reference to the above, except that in step (1), hexamethylene diisocyanate is added, specifically:

[0081] Step (1): 500 g of PVDF-HFP and 5 wt % of polyimide (based on the total weight of PVDF-HFP, aramid fiber, polyimide and hexamethylene diisocyanate) are respectively dissolved in N-methylpyrrolidone solvent, stirred evenly to form a high-temperature stable mixed solution, the dissolution time is 1 hour, and the stirring speed is 300 rpm; aramid fiber is slowly added to the mixed solution, ultrasonically dispersed for 30 minutes, and then 2 wt % of hexamethylene diisocyanate (based on the total weight of PVDF-HFP, aramid fiber, polyimide and hexamethylene diisocyanate) is added, and reacted at 100° C. for 1 hour to obtain a mixture I; the mixture I is sequentially subjected to a casting process and a drying process I, and the dried polymer film is placed in a vacuum hot press for molding to obtain a polymer substrate;

[0082] The rest remain unchanged to obtain a composite gel electrolyte membrane.

[0083] Example 5

[0084] This example is carried out in accordance with the method of Example 1, except that in step (3), an equal weight of carboxymethyl cellulose is used to replace the polyethylene oxide gelling agent, and the remaining substances and amounts remain unchanged, thereby obtaining a composite gel electrolyte membrane.

[0085] Comparative Example 1

[0086] This example is carried out in accordance with the method of Example 1, except that in step (1), aramid fiber is not added, and the remaining substances and amounts remain unchanged, thereby obtaining a composite gel electrolyte membrane.

[0087] Comparative Example 2

[0088] The method of Example 1 is followed, except that in step (1), the amount of PVDF-HFP is kept unchanged, the weight ratio of PVDF-HFP to aramid fiber is adjusted to 8:1, and the rest remain unchanged to obtain a composite gel electrolyte membrane.

[0089] Comparative Example 3

[0090] The method of Example 1 is followed, except that the operation in step (2) is not performed, but alumina powder is directly added in step (3) to obtain a mixture III, which is then coated on both sides of the polymer substrate to obtain a composite gel electrolyte membrane. Specifically:

[0091] Step (1): the same as in Example 1;

[0092] Step (3): Dissolve 200 g of the gelling agent polyethylene oxide and PVDF-HFP in 1 L of N-methylpyrrolidone respectively, mix and stir evenly, add 450 g of alumina ceramic powder, and stir evenly to obtain a mixture III; apply the mixture III evenly on the upper and lower surfaces of the polymer substrate by dip coating, and perform drying treatment III in turn.

[0093] The remaining formula and process parameters were the same as those in Example 1 to prepare a composite gel electrolyte membrane.

[0094] Test Case

[0095] The performance of the composite gel electrolyte membranes prepared in the examples and comparative examples was tested, and the test results are shown in Table 2.

[0096] Porosity test: The specific method is to use the water pressure method to measure the porosity.

[0097] Electrochemical performance test: At 25° C., 35° C. and 45° C., the ionic conductivity of the composite gel electrolyte membranes prepared in the above-mentioned embodiments and comparative examples was tested by electrochemical impedance spectroscopy (EIS).

[0098] Mechanical property test: The tensile strength of the composite gel electrolyte membrane prepared in the above-mentioned embodiments and comparative examples was tested using a universal material testing machine. The specific method is to take a sample with a length of 200 mm and a width of 15 mm, test rate: 200 mm / min, gauge length: 100 mm, fix the sample on the testing equipment, ensure that the sample is fixed vertically, the sample edge is flat and smooth, and the membrane surface is not damaged, click the "Reset" button on the controller, and then click the "Run" button. After the test is completed, data processing is performed in the software.

[0099] Cycle life test: 1000 charge and discharge cycles were performed at 25℃ and 60℃ to monitor the battery capacity retention rate and internal resistance change. The specific method is to use a mixture of LiFePO4, SP (conductive carbon black), PVDF (weight ratio 96:2:2) as the positive electrode, a mixture of artificial graphite, SP (conductive carbon black), CMC and styrene-butadiene rubber (weight ratio 95:1.5:1.5:2) as the negative electrode, Tianci EL-01A electrolyte and the composite gel electrolyte diaphragm prepared above, and use the traditional lamination process to make a lithium-ion battery for electrical performance testing.

[0100] Table 2

[0101]

[0102] It can be seen from the results in Table 2 that the composite gel electrolyte membrane provided by the present invention has significantly better thermal stability, mechanical strength and long cycle stability.

[0103] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite gel electrolyte membrane, characterized in that: The composite gel electrolyte membrane comprises a polymer substrate, and a ceramic coating and a gelling functional coating sequentially coated on both sides of the polymer substrate; The polymer substrate contains PVDF-HFP and aramid fiber in a weight ratio of 5-6:1; the gelling functional coating contains a gelling agent and PVDF-HFP in a weight ratio of 1:2-3.

2. The composite gel electrolyte membrane according to claim 1, characterized in that: The ceramic coating is selected from at least one of alumina ceramics, boehmite ceramics, zirconia ceramics, LATP ceramics, and LLZTO ceramics; And / or, the gelling agent is selected from at least one of polyethers, polyacrylonitrile, acrylic acid and its lipid polymers, polyvinyl chloride, polyamide, cellulose, polyethylene oxide, polypropylene oxide, and polyvinyl acetate; And / or, the aramid fiber has a length of 50-100 μm.

3. The composite gel electrolyte membrane according to claim 1, characterized in that: The polymer substrate further contains polyimide, and the content of the polyimide is 3-10wt% based on the total weight of the polymer substrate; And / or, the polymer substrate further contains diisocyanate, and the content of the diisocyanate is 1-5 wt % based on the total weight of the polymer substrate.

4. The composite gel electrolyte membrane according to claim 1 or 2, characterized in that: The total thickness of the composite gel electrolyte membrane is 10-30 μm; And / or, the thickness ratio of the polymer substrate, the ceramic coating and the gelation functional coating in the composite gel electrolyte membrane is 1:0.1-0.3:0.1-0.

3.

5. The composite gel electrolyte membrane according to claim 1 or 2, characterized in that: The composite gel electrolyte membrane has a porosity of 30-70% and an ionic conductivity of >2 mS / cm at 25°C; and / or, the tensile strength of the composite gel electrolyte membrane is ≥150kgf / cm2; And / or, the capacity retention rate of the composite gel electrolyte membrane under the conditions of 25° C. and 1000 charge and discharge cycles is ≥86%.

6. A method for preparing the composite gel electrolyte membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) in the presence of an organic solvent I, the components in the composition A are first mixed to obtain a mixture I; the mixture I is sequentially subjected to a casting process, a drying process I and a molding process to obtain the polymer substrate; The composition A contains PVDF-HFP, aramid fiber, and optionally polyimide and optionally diisocyanate; (2) performing a second mixing of the ceramic material and the organic solvent II to obtain a mixture II; applying the mixture II on both sides of the polymer substrate by a roller coating method, and performing a drying treatment II to obtain an intermediate diaphragm product; (3) In the presence of an organic solvent III, the gelling agent and PVDF-HFP are mixed for a third time to obtain a mixture III; the mixture III is coated on both sides of the intermediate diaphragm product by a dip coating method, and then a drying treatment III is performed in sequence to obtain the composite gel electrolyte diaphragm.

7. The method according to claim 6, characterized in that In step (1), the conditions of the tape casting process are controlled so that the coating thickness of the mixture I is 5-20 μm; And / or, the conditions of the drying treatment I include: temperature of 75-85° C., time of 0.5-1.5 h; And / or, the molding treatment is performed by hot pressing, and the conditions of the hot pressing include: a temperature of 100-120° C. and a time of 0.5-1.5 h.

8. The method according to claim 6 or 7, characterized in that: In step (2), the second mixing is performed at a pH value of 6.5-7.5; and / or, controlling the roller coating conditions so that the coating thickness of the mixture II is 1-5 μm; And / or, the conditions of the drying treatment II include: temperature of 75-85° C. and time of 0.5-1.5 h.

9. The method according to claim 6 or 7, characterized in that: In step (3), the dip coating conditions are controlled so that the coating thickness of the mixture III is 1-3 μm; And / or, the conditions of the drying treatment III include: a temperature of 55-65° C. and a time of 0.5-1.5 h.

10. Use of the composite gel electrolyte membrane according to any one of claims 1 to 5 in a lithium ion battery.